You'll be alright, kid [compact disc] - Warren, Alex, 2000- (Atlantic, 2025)
"Alex Warren's new album includes the smash hit single Ordinary. It also features Bloodline, his collaboration with Jelly Roll." --www.cvsmidwesttape.ca.